Aromatherapy Peppermint dapat Menurunkan Rasa Takut Terinfeksi Covid-19 pada Ibu Hamil: Peppermint Aromatherapy can Reduce Fear of Infecting Covid-19 in Pregnant Women - Riska Septiana; Hari Ghanesia Istiani; Rina Afrina (MPI Press, 2023)
Introduction: Covid-19 is an infectious disease that easily attacks anyone and can be bad for those who suffer from it. This creates a sense of fear for all residents, including pregnant women. Therefore, therapy is needed to reduce fear, namely peppermint aromatherapy. Objectives: This study aimed to determine the effect of giving peppermint aromatherapy to pregnant women who were confirmed to have Covid-19. Method: This study used a quasi-experimental design. Samples taken were 30 pregnant women patients at the hospital. Bina Husada. The instruments used were a fear level questionnaire, namely the FCV-19S or fear of Covid-19 Scale, and an observation sheet for the SOP for administering peppermint aromatherapy. Statistical test using Paired Samples T-test. Result: From univariate data, it was found that most of the fear of Covid-19 before being given peppermint aromatherapy was mostly at a moderate level in 20 people (66%) while after administration it was mostly at a moderate level in 19 people (63%). Based on the statistical test results, it is known that the p-value is 0.032 (p <0.05). Conclusion: There is an effect of fear of being infected with Covid-19 in pregnant women before and after being given peppermint aromatherapy.